Effect of combined fraction S1 and GM-H-1 (Citrinin) from Penicillium sp. H9318 on induction of cell cycle arrest and apoptosis in HT-29 cell line - Ooi, Suek Chin (2010)
Microfungi have been much sought after for its secondary metabolites to yield bioactive compounds that are widely investigated for its versatile usage in pharmaceutical areas. Recently, the production of small molecular inhibitors, particularly the inhibitors of protein phosphatase 1 (PP1) and protein phosphatase 2A (PP2A), are under intensive research in pursuit of its efficacy in the cancer therapeutic modalities. In our study, secondary metabolites were isolated from microfungi H9318, a Penicillium sp. H9318 was determined as a new strain of Penicillium citrinum as shown by the phylogenic study. Two fractions, S1 and GM-H-1, were isolated from H9318 strain and GM-H-1 was later structurally confirmed as Citrinin (CTN). Our study aims to elucidate cytotoxic mechanism of S1 and CTN on colon cancer cells, HT-29. It is known that CTN is a mycotoxin associated with hepatotoxicity and nephrotoxicity. Interestingly, CTN has also been reported to induce cell cycle arrest and apoptosis in various types of cells, including cancer cells. In an effort to attenuate the toxicity of CTN, a combination of S1 and CTN (S1 + CTN) was commenced to allow synergistic effect on the approach of anticancer regimen. Much evidence on the morphological, colorimetric and FACS (Fluorescent-activated cell sorting) assessment have reflected the pronounced inhibitory effect of S1 and CTN in combination on cell proliferation and mitotic progression. Together with the Western blot analysis, the level of phosphorylated-Extracellular-signal-regulated kinase (p-ERK1/2) was found elevated and phosphorylated-Retinoblastoma protein (p-RB) was decreased, indicating a possible activation of both proteins that is partly responsible for the mechanism in triggering G2/M phase cell cycle arrest as a consequence of S1 + CTN exposure. Luminogenic assay has shown suppression of Caspase 3/7 activity in an event of apoptosis occurred on HT-29 cells induced by S1 + CTN treatment. In line with this, FACS-analysed activation of pan-caspases was correlated with the induction of p-ERK1/2 and it is speculated that activity of ERK1/2 is maintained by certain caspases which in fact remains to be elucidated. Significantly, our data has provided an alternative agent which could be recommended in the study of cellular signal transduction pathway, that is, S1 as being recognised as a candidate PP1/PP2A inhibitor throughout a series of composite biochemical assays. However, it should be confirmed by more in depth studies and structural analysis. Presented here is the first report on the toxicity mechanism of CTN on HT-29 cells and presumably a cell-based model entity of the mode of action of S1 + CTN was described. In conclusion, S1 + CTN exerted anticancer activity on HT-29 cells by modulating the signaling pathways of ERK1/2 and RB proteins regulating cell cycle progression and apoptosis independent of Caspase 3/7.